Banking Efficiency Determinants in India: A Two-stage Analysis. (November 2019) - Goswami, Rishabh; Hussain, Farah; Kumar, Manish
This study aims at measuring the technical efficiency of banks in India and examining its determinants. Efficiency is said to be achieved if a bank is able to maximise its output subject to limited inputs. To obtain technical efficiency score, input-oriented Malmquist Data Envelopment Analysis is applied on two outputs and three input variables, based on a VRS (variable returns to scale) assumption. Three foreign banks—namely, A B Bank Ltd, Bank of Ceylon, and Citibank N A—and two Indian banks—namely, HDFC Bank and State Bank of India—are found to be most efficient during the study period. The efficiency scores when subsequently used as the dependent variable along with independent variables—bank size, capitalisation, liquidity risk, returns on assets, interest rate, credit risk, market concentration and gross domestic product (GDP)—in a panel regression analysis found the fixed effect model to be more appropriate in explaining the determinants. The results reveal that liquidity risk, returns on assets, credit risk, market concentration and GDP have a significant effect on the technical efficiency, while banks size, interest rate and level of capitalisation are found to be insignificant variables. JEL Classification: G21, C13, C60